Changes in the potential distribution of the guava fruit fly Anastrepha striata (Diptera, Tephritidae)under current and possible future climate scenarios in Colombia (2021)
Climate change has affected the geographical distributions of most species worldwide; in particular, insects of economic importance inhabiting tropical regions have been impacted. Current and future predictions of change in geographic distribution are frequently included in species distribution models (SDMs). The potential spatial distributions of the fruit fly Anastrepha striata Schiner, the main species of agricultural importance in guava crops, under current and possible future scenarios in Colombia were modeled, and the establishment risk was assessed for each guava-producing municipality in the country. SDMs were developed using 221 geographical records in conjunction with nine scenopoetic variables. The model for current climate conditions indicated an extensive suitable area for the establishment of A. striata in the Andean region, smaller areas in the Caribbean and Pacific, and almost no areas in the Orinoquia and Amazonian regions. A brief discussion regarding the area's suitability for the fly is offered. According to the results, altitude is one of the main factors that direct the distribution of A. striata in the tropics. The Colombian guava-producing municipalities were classified according to the degree of vulnerability to fly establishment as follows: 42 were high risk, 16 were intermediate risk, and 17 were low risk. The implementation of future integrated management plans must include optimal spatial data and must consider environmental aspects, such as those suggested by the models presented here. Control decisions should aim to mitigate the positive relationship between global warming and the increase in the dispersal area of the fruit fly. Keywords: Climate change; global warming; guava crops; modeling; species distribution.